Evaluation Of Faculty Teaching Performance in UndergraduateIslamic Education Management Programs - Al Haqqi; Fitri Oviyanti; Yuniar; Ahmad Zainuri (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
Higher education institutions are required to continuously improve learning quality, in which lecturers play a central role in designing, implementing, and evaluating instruction. This study aims to evaluate the teaching performance of lecturers in the Bachelor’s Program in Islamic Education Management at UIN Raden Fatah Palembang using the CIPP (Context, Input, Process, Product) evaluation model. A mixed-methods approach was employed by integrating quantitative and qualitative data. Quantitative data were collected through student questionnaires to measure satisfaction with teaching performance, while qualitative data were obtained from interviews, observations, and document analysis involving program leaders, lecturers, and students. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that lecturers’ teaching performance is generally in the “good” category. Instructional objectives are clearly defined and aligned with the Outcome-Based Education curriculum and institutional vision; inputs are supported by qualified lecturers, sufficient experience, adequate facilities, and relevant academic policies; the learning process is effectively implemented through varied teaching methods, positive interactions, and transparent assessment; and learning outcomes show that students demonstrate understanding, active participation, and achievement of course objectives. This study concludes that teaching performance at UIN Raden Fatah Palembang is satisfactory but requires continuous improvement, particularly in strengthening digital competence, optimizing educational technology, standardizing learning objective communication, and enhancing innovative teaching practices to improve educational quality and graduate competitiveness.